Território de gênero: da flexibilidade à precariedade do trabalho feminino no complexo de usinas hidrelétricas na cidade de Quevedos – Rio Grande do Sul - Duarte, Giovana (2022)
The city of Quevedos locates in the interior of Rio Grande do Sul State. Since the 20th century, it has been experiencing the impacts caused by interventions in the available natural resources in favor of large companies. Recently, four small power plants have been installed. So, they have triggered significant changes in the occupational structure of the place, from the incidence of more than 500 direct jobs and others outsourced. Such a context emerged with many workers from different geographies, from the northeast to the south of Brazil. At the same time, there was also a growing concentration of prostitution spaces. Thus, women started peripheral jobs and services and were socially and morally devalued. Therefore, the study analyzes the female workers' conditions in the complex of hydroelectric plants, in the city of Quevedos (RS), between 2018 to 2021, from the work and class experiences to understand the formation of a gender territory between the spaces of hydroelectric plants and prostitution. Then, it was possible to use qualitative research articulated with a triangulation of data from different sources such as the narrative interview technique, resources of life and oral histories, and documentary research for the women's world of work densification. The research indicates that gender territory alludes to common class experiences among women who work in the mills' internal jobs and prostitution. The conditions and relations of precarious work refer to long working hours, variable wages, forms of control, repression and overexploitation, expressive in the daily life of the sphere of production imposed harms to their well-being and coexisted with the need for geographically mobile workers. Both are deprived of stability and security, living on the fringes of risk and social vulnerability. However, they use sociability in their toil for nurturing and resistance strategies to keep themselves in occupations. In addition, they experience harsh gender oppression in the workplace. The territory is constituted by an objective and subjective point of view. The practical and symbolic dimensions denote the precariousness experienced in women's lives due to the impact of flexible working conditions and systematic inequalities of gender and race.